Palmitic Acid Methyl Ester and Its Relation to Control of Tone of Human Visceral Arteries and Rat Aortas by Perivascular Adipose Tissue - Wang, Ning; Kuczmanski, Artur; Dubrovska, Galyna; Gollasch, Maik (Frontiers in Physiology, 2018)
Background: Perivascular adipose tissue (PVAT) exerts anti-contractile effects on visceral arteries by release of various perivascular relaxing factors (PVRFs) and opening voltage-gated K+ (Kv) channels in vascular smooth muscle cells (VSMCs). Palmitic acid methyl ester (PAME) has been proposed as transferable PVRF in rat aorta. Here, we studied PVAT regulation of arterial tone of human mesenteric arteries and clarified the contribution of Kv channels and PAME in the effects. Methods: Wire myography was used to measure vasocontractions of mesenteric artery rings from patients undergoing abdominal surgery. Isolated aortic rings from Sprague-Dawley rats were studied for comparison. PVAT was either left intact or removed from the arterial rings. Vasocontractions were induced by external high K+ (60 mM), serotonin (5-HT) or phenylephrine. PAME (10 nM to 3 µM) was used as vasodilator. Kv channels were blocked by XE991, a Kv7 (KCNQ) channel inhibitor, or by 4-aminopyridine, a non-specific Kv channel inhibitor. PAME was measured in bathing solutions incubated with rat peri-aortic or human visceral adipose tissue. Results: We found that PVAT displayed anti-contractile effects in both human mesenteric arteries and rat aortas. The anti-contractile effects were inhibited by XE991 (30 µM). PAME (EC50 1.4 µM) was capable to produce relaxations of PVAT-removed rat aortas. These effects were abolished by XE991 (30 µM), but not 4-aminopyridine (2 mM) or NDGA (10 µM), a lipoxygenases inhibitor. The cytochrome P450 epoxygenase inhibitor 17-octadecynoic acid (ODYA 10 µM) and the soluble epoxide hydrolase inhibitor 12-(3-adamantan-1-ylureido)-dodecanoic acid (AUDA 10 µM) slightly decreased PAME relaxations. PAME up to 10 µM failed to induce relaxations of PVAT-removed human mesenteric arteries. 5-HT induced endogenous PAME release from rat peri-aortic adipose tissue, but not from human visceral adipose tissue. Conclusions: Our data also suggest that Kv7 channels are involved in the anti-contractile effects of PVAT on arterial tone in both rat aorta and human mesenteric arteries. PAME could contribute to PVAT relaxations by activating Kv7 channels in rat aorta, but not in human mesenteric arteries.